Zinc/aluminiumquinclorac layered nanocomposite modified multi-walled carbon nanotube paste electrode for electrochemical determination of bisphenol A - Norhayati Hashim (Tanjong Malim, 2019)
Zinc/aluminiumquinclorac layered nanocomposite modified multi-walled carbon nanotube paste electrode for electrochemical determination of bisphenol A by Norhayati Hashim